2018
DOI: 10.5194/se-9-1157-2018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of slope aspect on the microbial properties of rhizospheric and non-rhizospheric soils on the Loess Plateau, China

Abstract: Abstract. Slope aspect is an important topographic factor in the micro-ecosystem environment, but its effect on the microbial properties of grassland rhizospheric soil (RS) and non-rhizospheric soil (NRS) remain unclear. A field experiment was conducted at the Ansai Research Station on the Loess Plateau in China to test the influence of slope aspects (south-facing, north-facing, and northwest-facing slopes, all with Artemisia sacrorum as the dominant species) on RS and NRS microbial biomass carbon (MBC) conten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Microbial communities are sensitive indicators of vegetation and soil properties changes, and their interaction is considered to be the main driving factor of ecosystem functions [ 40 ]. Many studies have indicated that the difference in soil microbial community structure is mainly affected by the vegetation characteristics and soil properties [ 22 , 41 ]. The type of vegetation community determines the initial composition of the microbial community, and vegetation affects the structure of the microbial community by affecting the soil environment [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial communities are sensitive indicators of vegetation and soil properties changes, and their interaction is considered to be the main driving factor of ecosystem functions [ 40 ]. Many studies have indicated that the difference in soil microbial community structure is mainly affected by the vegetation characteristics and soil properties [ 22 , 41 ]. The type of vegetation community determines the initial composition of the microbial community, and vegetation affects the structure of the microbial community by affecting the soil environment [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that north slopes have higher microbial biomass carbon (MBC) and relative abundance of Gram-negative bacterial than south slope [ 20 ]. However, other studies have shown that the total phospholipid fatty acid, diversity of bacterial and fungal in the south slope were higher than that in north slope [ 22 ]. These results reflect the obvious influence of slope aspect on microbial community characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial communities are sensitive indicators of vegetation and soil properties changes, and their interaction is considered to be the main driving factor of ecosystem functions [33]. Many studies have indicated that the difference in soil microbial community structure is mainly affected by the vegetation characteristics and soil properties [19,34]. The PCoA and AMOSIM analysis showed the microbial community of the shady and sunny slope were differed.…”
Section: Relationship Among Vegetation Characteristics Soil Properties and Microbial Communitymentioning
confidence: 99%
“…Some studies have found that north slopes have higher microbial biomass carbon (MBC) and relative abundance of Gram-negative bacterial than south slope [17]. However, other studies have shown that the total phospholipid fatty acid, diversity of bacterial and fungal in the south slope were higher than north slope [19]. These results re ect the obvious in uence of slope aspect on microbial community characteristics.…”
Section: Introductionmentioning
confidence: 95%
“…Soil microorganisms release mineral elements that contribute to plant growth by driving organic matter and nutrient cycling in the soil, while plants transfer carbon and nitrogen to the soil through debris and root secretion (Kardol et al, 2006; Kuramae et al, 2011). Plant species have a decisive effect on soil microorganisms in their area (Ai et al, 2018). As a result, plant expansion affects soil microbial community structure (Stefanowicz et al, 2019; Yang et al, 2016), composition (Batten et al, 2006), and functions (Souza‐Alonso et al, 2014; Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%